Addressing genetic diversity and health inequities: RELIVAF’s proposal for Latin American pharmacogenomic guidelines - Quiñones, Luis A.; Martínez, Matías F.; Vargas, Rodrigo; Cerpa, Leslie C.; López-Cortés, Andrés; González-Martínez, Farith; Fonseca, Dora; Duconge, Jorge; Varela, Nelson M.; Lares-Asseff, Ismael; Redal, María Ana; Esperón, Patricia; et al. (Frontiers in Pharmacology, 2026)
Latin America’s exceptional genetic diversity, shaped by centuries of admixture among Native American, European, and African ancestries, presents both challenges and opportunities for pharmacogenomic implementation. Current guidelines by CPIC and DPWG, though foundational, are largely based on European and East Asian data, limiting their applicability in highly admixed populations. This article presents the rationale and methodology of RELIVAF (Latin American Network for the Implementation and Validation of Pharmacogenomic Clinical Guidelines), which aims to produce region-specific recommendations aligned with local genetic profiles, healthcare systems, and regulatory landscapes. The framework integrates international standards with country- and ancestry-specific allele frequencies, effect sizes, drug availability, and implementation constraints. It also incorporates educational strategies to promote pharmacogenomic literacy among healthcare professionals. Three gene-drug pairs were prioritized for initial guideline development: DPYD-fluoropyrimidines, TPMT/NUDT15–thiopurines (paediatric ALL), and CYP2C9/VKORC1-coumarin anticoagulants (e.g., warfarin, acenocoumarol). Selection was based on clinical relevance, allele frequency variability, and potential public health impact. By leveraging regional data and collaborative expertise, RELIVAF aims to deliver actionable, equitable, and context-specific pharmacogenomic guidance, advancing precision medicine in Latin America and serving as a model for other underrepresented regions.